Designing Mini Master Plan For Developing E-learning Content In Project Management Course (case Study : Project Procurement Knowledge) - Mifthahul Fathia; Devi Pratam; Muhammad Azani Hasibuan (eProceedings of Engineering, 2019)
Abstract— The application of smart technology must be undertaken to achieve innovative learning and challenge of the era industrial revolution 4.0. Telkom University especially at the faculty of Industrial Engineering has applied the concept of E-learning in several courses. Therefore, the amount of material make students difficult in understanding project management materials. The design of e-learning content is very important because it affects the level of understanding of students to project management course The author tested the design of e-learning content at the procurement knowledge area of Project Management. The media chosen to make e-learning content is video. The first step that needs to do before making a video learning is to make a project management plan. Planning can maintain the project under control and help everyone to participate in right way. To meet costumer expectation, design sprint is needed for generates idea from team member to developing E-learning content. The result of this study, student performance has increased after watching the video learning about the project procurement knowledge.